Analisis Pengaruh Produksi dan Ekspor Kopi terhadap PDRB di Pulau Jawa (2015–2024) - Syifa Ardhana; Adelia Sifadilla; Nazwa Silva Fauziah; Nindya Kirana Putri Sandy; Ahmad Setiawan Nuraya (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study analyzes the effect of coffee production and exports on the Gross Regional Domestic Product (GRDP) of Java Island for the period 2015–2024. Java Island plays a strategic role in the national economy, both in the industrial and agricultural sectors, including coffee as one of its key plantation commodities. Using a qualitative descriptive approach with time-series secondary data sourced from the Central Statistics Agency (BPS), the Ministry of Agriculture, the Ministry of Trade, and the International Coffee Organization (ICO), this study examines trends in coffee production, export performance, and their relationship to GRDP. The findings show that coffee production in Java demonstrated an overall increasing trend, reaching a peak of 807.58 thousand tons in 2024, although minor fluctuations occurred in certain years. Coffee exports were also volatile, with notable declines in 2018 and 2023 due to climate disruptions and global demand pressures, while 2024 recorded the highest export value at USD 1,624,121.5 million. The relationship between coffee production and exports toward GRDP is positive, as increasing production and export activity expand the value added in the plantation subsector and stimulate related economic activities. East Java demonstrated the strongest contribution due to its large production base and export infrastructure, while West Java excelled in product quality and premium market access. The study concludes that improving coffee quality, post-harvest processing, and export market expansion are essential for maximizing coffee’s contribution to regional economic growth.